Effectiveness of Counseling on Quality of Life of Patients with HIV/AIDS in Selected ART Centers of Mangalore - ABRAHAM, SURYA; D SILVA, FATIMA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Introduction: Acquired immunodeficiency syndrome (AIDS), the outcome of a viral infection human immunodeficiency virus (HIV) has not only affected individuals physically, but individuals have also lost their social identity due to societal stigma and discrimination. Counseling is considered a powerful tool of creating positive attitudes among these patients and thus enhancing their quality of life (QOL). Objective: The aim was to explore the physical and psychosocial problems of people living with HIV/AIDS (PLWHA) and evaluate the effectiveness of counseling on these patients. Materials and Methods: A pre-experimental design was adopted for the study. A total of 100 samples were selected through purposive sampling technique. Demographic proforma, sign and symptom check-list, WHOQOL-BREF scale were the instruments utilized for the study. The data were analyzed using SPSS 16. Results: Majority of the subjects were males and below 41 years. 75% of the subjects were married and belonged to the rural community. About 53% had primary education. Though 77% were on antiretroviral therapy (ART) therapy, most of the subjects had a CD4 count of <410 cells/mm3. The common physical ailment faced by HIV subjects was gas/bloating and thirst and psychologically most of them found their life to be less meaningful. Pre-intervention, QOL was poor among HIV subjects. Counseling significantly revealed a positive change in the QOL of these subjects (p<0.005). The study findings also unveiled a significant association of taking ART medication and QOL (p=0.005). Conclusion: The experience of HIV/AIDS is indeed stressful event. Health care team members must aim to address the psychosocial and emotional concerns of these patients, along with their medical needs. The study has proved that nurses play a vital and effective role in enhancing the QOL of these patients through counseling. Keywords: Human immunodeficiency virus, Acquired immunodeficiency virus, Quality of life, People living with human immunodeficiency virus/ acquired immunodeficiency syndrome.